Comportamento não linear de cascas cilíndricas enrijecidas - Chamberlain Pravia, Zacarias Martin (1990)
A mathematical model for nonlinear static analysis of axially compressed stringer stiffned cylindrical shells is presented. This model is based on a modal combination from a general solution of the differential equations of dynamic equilibrium for an isotropic cylindrical shell. The nonlinear equilibrium equations are obtained through variational principles and small initial geometric imperfections are considered. An adopted yield criterion allows for failure loads estimates, besides classical critical loads.